AUGE Y OCASO DEL CARBÓN MINERAL EN URUGUAY. UN ANÁLISIS HISTÓRICO DESDE FINES DEL SIGLO XIX HASTA LA ACTUALIDAD*: The rise and fall of mineral coal in Uruguay. A historical analysis from the last decades of the 19th century to the present. (4th December 2013) - Bertoni, Reto; Román, Carolina
ABSTRACT: The study of the rise and fall of mineral coal as an energy source can shed light on the characteristics of energy transition in Uruguay. This article presents historical series of coal consumption for Uruguay since the last decades of the 19 th century until nowadays (1879-2011). The "coal era" can be placed in the first decades of the 20 th century. The use of this mineral in four sectors may explain the dynamic of the coal consumption as a result of different trajectories that characterize the Uruguayan energy transition pattern of stops and goes. In addition, the article put forward three factors to explain the decisions to shift from coal to other energy sources: relative prices and freights, technological innovations and institutional aspects. RESUMEN: El análisis del auge y ocaso del carbón mineral como fuente energética en Uruguay aporta información para entender las características de la transición al petróleo. Este trabajo presenta una serie de consumo de carbón mineral en Uruguay desde fines del siglo XIX hasta la actualidad (1879-2011). La «era del carbón» se ubica en las primeras décadas del siglo XX. La demanda efectiva de cuatro sectores contribuye a explicar el comportamiento del carbón como el resultado de diferentes trayectorias que caracterizan el patrón uruguayo de retrocesos y recuperación. Además, se discuten tres factores explicativos —precios y fletes, innovaciones tecnológicas y aspectos institucionales— que están detrás de las razones que impulsaron a los actores estratégicos a adoptar fuentes energéticas modernas.